PELAKSANAAN SUPERVISI MANAJERIAL PENGAWAS SEKOLAH PADA SEKOLAH MENENGAH ATAS SWASTA DI KOTA BANDA ACEH - Syarwan Joni; Djailani AR; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: The school supervisor is one of the elements that have an important role in improving the quality of education through an increase in the ability of school personnel working in the management of the school administration. This study aimed to get an idea of the implementation of managerial supervision on Private High School Banda Aceh. By using descriptive research methods, qualitative approach, and data collection techniques such of observation, interviews and documentation. Research subjects to the school supervisors, headmaster, and staff at private high school in Banda Aceh. The results of research have been analyzed qualitatively show that: The school supervisors has prepared supervision program together at the beginning of the school year, coordinated by the Supervisory Coordinator, organized program assessment results-oriented, monitoring and coaching from previous year. Managerial supervision carried out by applying a procedure that starts with pre supervision activities through coordination and socialization to target schools (sekolah binaan). Furthermore, the scope of supervision is started with the performance appraisal headmaster, teachers and educational staff focused on the management of the school administration. Monitoring activities are directed at the implementation of eight National Education Standards (NES). While development activities directed to school management in order to work in accordance with their duties and functions. Obstacles of implementation managerial supervision is supervisors's own self and from the field, namely: supervisors has not been uniform level of understanding, number of supervisors is not comparable with the number of schools that fostered. Obstacles in the field, namely; number of administrative staff of the school is not sufficient. Based on the research results, it is suggested that the implementation of managerial supervision implemented more intensively to improve job skills. Keyword: Managerial Supervision, School Supervision and School Manager   Abstrak: Pengawas sekolah merupakan salah satu elemen yang memiliki peranan penting dalam meningkatan kemampuan kerja personil sekolah terutama dalam hal pengelolaan sekolah. Salah satu tugas pengawas untuk mengendalikan pengelolaan sekolah dilakukan melalui pelaksanaan supervisi manajerial. Tujuan penelitian ini untuk mendapat gambaran pelaksanaan supervisi manajerial yang dilaksanakan pengawas pada SMA Swasta di Kota Banda Aceh. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Data yang diperoleh dalam penelitian ini melaui observasi, wawancara dan studi dokumentasi, sedangkan yang menjadi subjek penelitian adalah pengawas sekolah, kepala sekolah, dan tenaga kependidikan. Hasil penelitian menunjukkan bahwa: Para pengawas sekolah menyusun program supervisi secara bersama dan dikoordinir oleh Kordinator Pengawas (KORWAS). Program yang disusun sudah mengikuti pedoman dan berorientasi pada hasil supervisi tahun sebelumnya. Supervisi manajerial dilaksanakan melalui kegiatan pra supervisi dan selanjutnya melakukan tiga tahapan kegiatan, yaitu penilaian kinerja kepala para pengelola sekolah, kegiatan pemantauan pada pelaksanaan delapan Standar Nasional Pendidikan (SNP). Sedangkan kegiatan pembinaan mengarahkan para pengelola sekolah agar dapat bekerja sesuai dengan tugas pokok dan fungsinya. Hambatan pelaksanaan supervisi manajerial dari pengawas sendiri dan dari lapangan, yaitu: tingkat pemahaman pengawas belum seragam, sedangkan hambatan dilapangan staf pelaksana adminsitrasi sekolah belum mencukupi. Berdasarkan hasil penelitian disarankan agar pelaksanaan supervisi manajerial dilaksanakan lebih intensif untuk meningkatkan keterampilan kerja tenaga kependidikan. Kata Kunci: Supervisi Manajerial, Pengawas Sekolah dan Pengelola Sekolah